Development of table tennis launcher - Liew, Xiu Qing (2017)
Table tennis launcher is a training tool which focuses to enhance and improve player skills. The object of the project is to develop an electronic controlled training tool that can be retrofitted on a standard table tennis table. The design requirement starts with acquisition of launching speed and trajectory during a training session using Yawcam and GIMP as well as webcam acquired at 8 frame per second. The prototype consists of two Brushless DC (BLDC) motors, two Electronic Speed Controller, PWM speed controller, ball feeding system and momentum launching instrumentation, as well as controller console. All of these is powered by 11.1 V 2200 mAh lithium polymer battery. The motor shaft is fitted with counter rotating elastomer wheels to increase the contact surfaces of rollers and balls. The angular speed of the rollers are controlled by the PWM speed controller up to nominal launching speed of 1 Om/s. The duration required to displace the ball is measured by the Light Dependence Resistor (LDR), laser emitter and optical arrangement instrumentation. An Arduino Mega 2560 is used to acquire the duration as well as the controlling the servo control feeding system. A Bluetooth module was used as a wireless protocol to allow implementation of voice control by using Android hand phone and open source BT Voice Control Applications. The performance of the table tennis launcher was evaluated on the basis of launching distance, consistency, repeatability and product satisfaction survey. It was found that the 1Om/s launching speed reached acceptable length with 2m. It also showed that the feeding system works fine. The voice control application can remotely control the frequency of ball feeding from certain distance. The survey result also showed that the system can be used as an alternative tool for training.